ANALISIS PENGGUNAAN MEDIA YOUTUBE TERHADAP MOTIVASI BELAJAR MAHASISWA PADA MATA KULIAH STATISTIK PENDIDIKAN - Amalia Nurjannah (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
This study aims to determine how to analyze the use of youtube media on studentlearning motivation in educational statistics courses. This research uses descriptivequalitative method. The research sample were 16 students taken using purposive samplingtechnique. The data collection technique uses a questionnaire. The data analysis techniqueused in this research is descriptive analysis of percentages. The results of the researchshow that the use of youtube media in educational statistics courses has a positive effect onlearning because it can make students very motivated and anthusiastic in learning. Thiscan be seen from the average of all indicators of student learning motivation, namely thepercentage is 80,49% in the high category. Therefore, this youtube media can berecommended for use as learning media in other courses